Screening for the FMR1 premutation in Greek patients with late-onset movement disorders. (February 2023) - Kartanou, Chrisoula; Seferiadi, Maria; Pomoni, Stella; Potagas, Constantin; Sofocleous, Chrystalena; Traeger-Synodinos, Joanne; Stefanis, Leonidas; Panas, Marios; Koutsis, Georgios; Karadima, Georgia
Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a late-onset, X-linked, neurodegenerative disorder that affects premutation carriers of the FMR1 gene. FXTAS is often misdiagnosed as spinocerebellar ataxia (SCA) or Parkinson's disease (PD). Herein, we sought to investigate the frequency, genotypic and phenotypic profile of FXTAS in two cohorts of Greek patients with late-onset movement disorders, one with cerebellar ataxia and the other with PD. In total, 90 index patients with late-onset cerebellar ataxia and 171 with PD were selected. None of the cases had male-to-male transmission. Genetic screening for the FMR1 premutation was performed using standard methodology. The FMR1 premutation was detected in two ataxia patients (2.2%) and two PD patients (1.2%). Additional clinical features in FXTAS patients from the ataxia cohort included neuropathy, mild parkinsonism, cognitive impairment and pyramidal signs. The FXTAS patients from the PD cohort had typical PD. We conclude that, in the Greek population, the FMR1 premutation is an important, albeit rare, cause of late-onset movement disorders. Routine premutation screening should be considered in SCA panel-negative late-onset ataxia cases. Directed premutation screening should be considered in all ataxia and PD cases with additional features suggestive of FXTAS. Our study highlights the importance of FMR1 genetic testing in the diagnosis of late-onset movement disorders. Highlights: We screened Greek patients with late-onset ataxia or PD for the FMR1 premutation. FXTAS was diagnosed in 2.2% of late-onset ataxias and 1.2% of PD. FXTAS is an important, albeit rare, cause of late-onset movement disorders in Greece. Screening for FXTAS should be considered in SCA panel-negative Greek ataxia patients. This is the first study of FXTAS in the Greek population.